Factors Affecting Youth Unemployment in Nepal - Khatri, Bishnu B.; Poudel , Omkar; Acharya, Pradeep (Molung Educational Frontier, 2025)
Youth unemployment remains a critical socio-economic challenge in Nepal, despite notable economic growth and substantial remittance inflows. This study examines the determinants of youth unemployment, focusing on economic, demographic, and policy-related factors such as GDP growth, remittances, foreign direct investment (FDI), population growth, and trade openness. Utilizing secondary time series data from 1993 to 2023, the research applies the Autoregressive Distributed Lag (ARDL) model, complemented by unit root tests and co-integration analysis, to evaluate short- and long-term relationships. The findings indicate that while GDP growth positively influences youth labor force participation, remittances and FDI contribute to higher unemployment by failing to create sustainable domestic job opportunities. Population growth and urbanization further exacerbate unemployment challenges, and the impact of trade openness is mixed, with short-term benefits overshadowed by potential long-term job losses. These results underscore structural inefficiencies in Nepal’s labor market. The study concludes that policy interventions are essential to ensure that economic growth translates into inclusive employment opportunities for the youth. Emphasizing targeted investment in labor-intensive industries and addressing demographic pressures are vital for mitigating youth unemployment. This research provides novel insights by integrating FDI and trade openness into the analysis, offering a comprehensive understanding of youth unemployment dynamics in Nepal. Future research should focus on the sectoral distribution of FDI, the role of technology in employment, and the effectiveness of government programs in reducing youth unemployment.